2016
DOI: 10.13102/sociobiology.v63i2.946
|View full text |Cite
|
Sign up to set email alerts
|

Risk of local extinction and genetic diversity of Melipona quadrifasciata (Apidae: Meliponini) in a possible Northeastern limit of its distribution in Brazil

Abstract: Fig 6.Haplotype network generated by the comparison of DNA sequences from the cytochrome b region. Population of M. quadrifasciata from semiarid Region (Caatinga) and from the mouth of river São Francisco are represented by dark grey and light grey respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…We have found that the diversity of microorganisms associated with these bees is greater than observed in Africanized Apis mellifera (Honeybee). The microbial biodiversity present in stingless bees is important and yet vulnerable since these bees are in danger of extinction due to loss of neotropical habitat by deforestation and excessive use of pesticides [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…We have found that the diversity of microorganisms associated with these bees is greater than observed in Africanized Apis mellifera (Honeybee). The microbial biodiversity present in stingless bees is important and yet vulnerable since these bees are in danger of extinction due to loss of neotropical habitat by deforestation and excessive use of pesticides [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Here, we only used linear morphometric characters, but other morphological characters can also be considered for the same purpose. For example, geometric morphometrics based on landmarks on the forewing have been applied to investigate morphological variation of Melipona quadrifasciata populations (Araújo et al 2016), which can overcome the problem of linear variables being highly related in multivariate morphometrics (Owen 2012). Color patterns can also be used for specific taxa with distinct color variation (Batalha-Filho et al 2010).…”
Section: Discussionmentioning
confidence: 99%